Front Cover. (27th October 2019) - Wilson‐Stewart, Kelly; Hartel, Gunter; Fontanarosa, Davide
Abstract : The cover image is based on the Original Article Occupational radiation exposure to the head is higher for scrub nurses than cardiologists during cardiac angiography by Kelly Wilson‐Stewart, Davide Fontanarosa, and Gunter Hartel, https://doi.org/DOI.10.1111/jan.14085